PEMULIHAN EKOSISTEM PESISIR GILI LABAK: TRANSPLANTASI KARANG, PENANAMAN 100 BIBIT CEMARA, DAN AKSI BERSIH PANTAI - Achmad Fachrudin Syah; Herlambang Aulia Rahman; Hidayu Al-Saari; Abdul Rozak Bachri; Dimas Chandra Winata; M. Athoillah An-Nafi'; Nur Shamira Jamil Nasri; Nur Fatin Aini Fekri Abidin (Jurnal Abdi Insani, 2026)
Gili Labak Island is one of the marine tourism destinations in Sumenep Regency that has a coastal ecosystem vulnerable to the pressures of tourism activities. The increase in the number of tourists without proper environmental management has caused damage to coral reefs and coastal erosion. This condition has reduced the quality of the environment and the beauty of the coastline. Conservation efforts through coral transplantation and casuarina tree planting are needed to maintain the sustainability of the ecosystem and tourism. In an effort to maintain the sustainability of this ecosystem, the “spider” frame is one of the most reliable transplantation methods due to its adaptive structure and efficient support for coral growth. The activities were carried out with the involvement of the community, students, and the village government. The methods used included environmental education, coral transplantation using spider frames, and the planting of 100 casuarina seedlings as an effort to rehabilitate the coastal ecosystem and sustainable tourism. These community service activities went well according to plan. Ten spider frames were successfully installed in shallow waters for coral transplantation, while one hundred casuarina seedlings were planted in coastal areas prone to abrasion. The active participation of the community, the supervisory group (Pokmaswas), and students from SMP Negeri 2 Saronggi contributed to the success of the activity. The coastal environment looks cleaner after the beach clean-up. This activity demonstrates the integration of marine and terrestrial conservation in supporting sustainable marine tourism management. With improved conditions, it is hoped that this will increase the number of tourists visiting and the economic level of the community on Gili Labak Island.